Low‐Intensity Ultrasound Upregulates the Expression of Cyclin‐D1 and Promotes Cellular Proliferation in Human Mesenchymal Stem Cells. Issue 4 (22nd January 2018) - Budhiraja, Gaurav; Sahu, Neety; Subramanian, Anuradha
Abstract : Human mesenchymal stem cells (hMSCs) hold great potential for cellular based therapeutics and tissue engineering applications and their expansion is an interesting prospect due to their low availability from in vivo sources. Therefore, this study investigated the effect of continuous‐wave low‐intensity ultrasound (LIUS) at 5.0‐MHz and 14.0‐kPa (<20 mW cm −2 ) on the proliferative capacity, colony‐formation efficiency, genetic stability, and differentiation potential of hMSCs. Additionally, potential signaling pathways involved in LIUS‐mediated proliferation of hMSCs are studied. Compared to non‐stimulated controls, LIUS‐treated hMSCs shows a 1.9‐fold greater colony‐forming efficiency and 2.5‐fold higher rate of cell proliferation, respectively. Differential staining and qRT‐PCR analysis for selective chondrogenic, osteogenic, and adipogenic markers further confirmed that the LIUS treatment did not impact the multipotency of hMSCs. LIUS‐treated hMSCs expressed normal male karyotype. The synthesis of cyclin‐D1, a master regulator of cellular proliferation, is upregulated under LIUS and its enhanced mRNA expression under LIUS is noted to be mediated by the activation of both MAPK/ERK and PI3K/AKT pathways. In conclusion, LIUS promotes proliferation and self‐renewal capacity of hMSCs. Abstract : Low‐intensity ultrasound (LIUS) at 5.0 MHz and 14 kPa enhances the proliferative capacity and colony‐forming efficacy while maintaining genetic stability and differentiation potential of mesenchymal stem cells. Increased cell proliferation under LIUS seems to be due to increased cyclin D1 expression, notably via the MAPK/ERK and P13/AKT pathways.